2022
DOI: 10.3389/fpsyt.2021.704564
|View full text |Cite
|
Sign up to set email alerts
|

Group-Based Online Job Interview Training Program Using Virtual Robot for Individuals With Autism Spectrum Disorders

Abstract: The rapid expansion of online job interviews during the COVID-19 pandemic is expected to continue after the pandemic has subsided. These interviews are a significant barrier for individuals with autism spectrum disorders (ASD). There is little evidence-based training for online job interviews for individuals with ASD, and the development of new trainings is expected. In an effort to facilitate online job interview skill acquisition for individuals with ASD, we developed a group-based online job interview train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The scripts of the mock interviews varied slightly across sessions to promote engagement but followed the same basic structure. (Examples of scripts are provided in Supplementary Material 2) The questions asked in the interview for the participants were the same as those used in previous studies (9,11,32) targeting individuals with ASD. Through these experiences, we realized these questions are relevant.…”
Section: Methodsmentioning
confidence: 99%
“…The scripts of the mock interviews varied slightly across sessions to promote engagement but followed the same basic structure. (Examples of scripts are provided in Supplementary Material 2) The questions asked in the interview for the participants were the same as those used in previous studies (9,11,32) targeting individuals with ASD. Through these experiences, we realized these questions are relevant.…”
Section: Methodsmentioning
confidence: 99%
“…However, many hurdles prevent individuals with ASD from concentrating on online job interview training. In our previous study, we found that individuals with ASD had higher interpersonal tension during online interview training and lower motivation in an online job interview setting ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike humans, virtual humanoid robots operate in predictable and lawful systems and, thus, can provide a highly structured learning environment that allows individuals with ASD to focus on relevant stimuli. Individuals with ASD may be highly motivated to communicate with virtual humanoid robots and exhibit social behaviors toward them ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations